Larvicidal activity of Bacillus thuringiensis strains against Aedes aegypti and Culex quinquefasciatus mosquitoes - Prakai Rajchanuwong; Sawaporn Peaboon; Ratchadawan Ngoen-Klan; Atsalek Rattanawannee; Atirat Noosidum; Boonhiang Promdonkoy; Jariya Chanpaisaeng; Theeraphap Chareonviriyaphap (Current Research in Parasitology and Vector-Borne Diseases)
Organophosphates, carbamates and synthetic pyrethroids are commonly used in Thailand to control mosquito vectors; however, long-term use of insecticides in vector control has led to the rapid development of insecticide resistance. In this study, we screened Bacillus thuringiensis strains as biological control agents for potential toxins against mosquito larvae as an additional control tool. Preliminary bioassays conducted on 434 strains demonstrated that 41 strains (11.64%) and 14 strains (3.97%) achieved 100% mortality against Ae. aegypti and Cx. quinquefasciatus larvae, respectively. Three strains (JC690, JC691, and JC699) showed toxicity to both mosquito species, compared with the reference Bti strain. Strain JC691 demonstrated the highest efficacy against Ae. aegypti and Cx. quinquefasciatus, with an LC50 value of 6.96 × 104 CFU/ml and 1.16 × 103 CFU/ml, respectively. A comparison of LC50 values revealed that JC691 exhibited higher efficacy against Cx. quinquefasciatus than that by Bti (Bti LC50: 8.89 × 10⁴ CFU/ml) but lower efficacy against Ae. aegypti (Bti LC50: 1.99 × 10³ CFU/ml). Scanning electron microscopy revealed that JC690, JC691, and JC699 are rod-shaped, have oval spores, and produce bi-pyramidal crystal proteins. Protein profile analysis using SDS-PAGE demonstrated distinct differences between these Thailand strains (JC690, JC691, and JC699) and the reference Bti strain. All three Thailand strains contained cry1I and cry2A genes, and only JC691 harbored the cry32 gene. Bayesian inference and maximum likelihood phylogenetic analyses of cry32 indicated that the partial sequences of cry32 in JC691 from Thailand were distinct from those of other B. thuringiensis strains from different countries. This study demonstrates the potential of JC690, JC691, and JC699 as biocontrol agents for Ae. aegypti and Cx. quinquefasciatus.